Effective microbial bioremediation via the multi-omics approach: An overview of trends, problems and prospects - Yunusa, Y.R.; Umar, Z.D. (UMYU Journal of Microbiology Research)
Techno-industrial advancements the world over had led to the generation of hazardous environmental pollutants. Microbial bioremediation offers the best alternative for the removal of these pollutants. The most recent advancements in microbial bioremediation were catalyzed by the advent of various tools that enable the study microbes at levels of sophisticated detail, including genome analysis tools (genomics), protocols for analyzing expressed proteins and enzymes or proteomes (proteomics), techniques of analyzing ribonucleic acids (RNAs) transcriptomes (transcriptomics), and tools for analyzing metabolic end products/metabolomes (metabolomics). The twenty first century is witnessing an outpour of developments in the application of omics approaches in effective microbial bioremediation, thus, this paper attempts to review some of the most significant insights gained from relatively recent studies over a period of two decades (2000-2020) in the applications of multi-OMICS in microbial bioremediation, including trends and cutting-edge researches. We aim to highlight, particularly, the challenges that need to be overcome before OMICs approaches are successfully enshrined in microbial bioremediation, especially in developing countries. The strategies for overcoming such challenges, and the prospects achieved were also outlined. In the coming years, we envision further researches involving the application of multi-OMICs approach in microbial bioremediation potentially revolutionizing this field, opening up research avenues, and leading to improvements in bioremediation of polluted environment.